Bidirectional Interaction Between Cancer Cells and Platelets Provides Potential Strategies for Cancer Therapies - Yu, Liuting; Guo, Yao; Chang, Zhiguang; Zhang, Dengyang; Zhang, Shiqiang; Pei, Hanzhong; Pang, Jun; Zhao, Zhizhuang Joe; Chen, Yun (Frontiers in Oncology, 2021)
Platelets are essential components in the tumor microenvironment. For decades, clinical data have demonstrated that cancer patients have a high risk of thrombosis that is associated with adverse prognosis and decreased survival, indicating the involvement of platelets in cancer progression. Increasing evidence confirms that cancer cells are able to induce production and activation of platelets. Once activated, platelets serve as allies of cancer cells in tumor growth and metastasis. They can protect circulating tumor cells (CTCs) against the immune system and detachment-induced apoptosis while facilitating angiogenesis and tumor cell adhesion and invasion. Therefore, antiplatelet agents and platelet-based therapies should be developed for cancer treatment. Here, we discuss the mechanism underlying the bidirectional cancer-platelet crosstalk and platelet-based therapeutic approaches.